Comparative evaluation of sealing of ProRoot MTA and Bio MTA in canal obturation by fluid infiltration - Abbasali Khademi; Seyed Amir Mousavi; Azizolah Moraditalab; Shirin Shahnaseri; Saber Khazaei; Reyhaneh Tajali (Tehran University of Medical Sciences, 2018)
Background and Aims: Microorganisms are the main cause of pulpal and periapical diseases. The most important failure factor is the lack of proper seals for the canal, resulting in microbial leakage. Therefore, the purpose of this study was to evaluate the sealing ability of ProRoot MTA and Bio MTA in canal obturation using fluid infiltration. Materials and Methods: In this experimental study, 46 extracted mandibular premolar single canal teeth were used. After preparing and disinfecting the teeth with 3% sodium hypochlorite, their crowns were cut off from the cement-enamel junction. The teeth were then randomly divided into four groups: Group 1 (n=20) Bio MTA, Group 2 MTA ProRoot (n=20), negative and positive control groups, each of them contained 3 teeth. The preparation of teeth was performed using the step back method. The filled teeth were then evaluated by fluid filtration for leakage prevention. Data were analyzed by Mann-Whitney test and Tukey test (α=0.05). Results: The results of statistical analysis showed that there was no significant difference between the MTA ProRoot and Bio MTA in sealing ability (P>0.05). That micro leakage is less in the Bio MTA group than in the ProRoot MTA group, but the difference was not significant. Conclusion: This study showed that MTA ProRoot and Bio MTA can be used as appropriate canal filling materials.